Characterization of a circular plasmid from Borrelia burgdorferi, etiologic agent of Lyme disease. - Hyde, F W (1988)
Borrelia burgdorferi, the etiologic agent of Lyme disease, was recently shown to contain plasmid DNA. Two plasmid species have been described in strain CT1, a Wisconsin tick isolate: a 9.2-kilobase entity; and a larger, 70-kilobase entity. Characterization of the 9.2-kilobase entity by using DNase I and restriction endonucleases demonstrated that the plasmid is supercoiled and exists as a stable dimer in this strain. The role played by the plasmid in B. burgdorferi is unknown.